Optimal Selection of Multicomponent Matching Layers for Piezoelectric Transducers using Genetic Algorithm - Tadeusz GUDRA; Dariusz BANASIAK (Archives of Acoustics)
One major problem in the design of ultrasonic transducers results from a huge impedance mismatch between piezoelectric ceramics and the loading medium (e.g. gaseous, liquid, and biological media). Solving this problem requires the use of a matching layer (or layers). Optimal selection of materials functioning as matching layers for piezoelectric transducers used in transmitting and receiving ultrasound waves strictly depends on the type of the medium receiving the ultrasound energy. Several methods allow optimal selection of materials used as matching layers. When using a single matching layer, its impedance can be calculated on the basis of the Chebyshev, DeSilets or Souquet criteria. In the general case, the typically applied methods use an analogy to a transmission line in order to calculate the transmission coefficient T. This paper presents an extension of transmission coefficient calculations with additional regard to the attenuation coefficients of particular layers. The transmission coefficient T is optimised on the basis of a genetic algorithm method. The obtained results indicate a significant divergence between the classical calculation methods and the genetic algorithm method.